La utilización de los títeres y su relación con el lenguaje oral de los niños y niñas de 5 a 6 años, de primer grado de educación general básica del centro educativo intercultural “Inti Pakari” del cantón Lago Agrio, provincia de Sucumbíos, en el periodo lectivo 2013 -2014”. Lineamientos propositivos - Chile de la Cruz, Luz Aracely (2014)
THIS RESEARCH REFERS TO "THE PUPPETS USE ANDITS RELATIONINTO ORAL BASÍC GENERAL EDUCATION FIVE TO SIX, YEARS OLD CHILDREN ORAL LANGUAGE“INTI PAKARI” INTERCULTURAL CENTER LAGO AGRIO CANTÓN, PROVINCE DE SUCUMBÍOS PERIODE 2013-2014. PROPOSITIONAL GUIDELINES The general objective: was to determine the association between Puppet and Oral Language children of First Grade Students "IntiPakari"Intercultural Center School The methodology used was based on the following methods: Inductive, Deductive, Analytical, Synthetic and Statistical Model two techniques and instruments were applied: a survey of teachers, to identify the application and the type of puppets used in their teaching practice; and the Zimmerman test applied to children, to assess the oral language. 100% of the teachers surveyed said that if you apply the puppets as a teaching resource in their teaching practice with children. This makes the class is motivating and artistic. Test the application of Zimmerman to children concluded that: 83% of the children, after applying the test obtained from normal development Speaking, 8% and 7% excellent low. Oral Language is very important in early childhood education. Children are learning to speak, the van needs it, expanding the vocabulary spontaneously combining articulating sounds and new words to their oral language, for this there is a speaker and a transmitter